Implementasi Nilai-Nilai Islam Nusantara di Lembaga Pendidikan Islam: (Studi Kasus Di SMPI Al-Maarif 01 Singosari) - Erfina (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2022)
The idea and methodology of Islam Nusantara is an axiology of text that was echoed by Walisongo as a result of the dialectic between the text and the local cultural reality. The basic principles or values ​​of Islam Nusantara are not only practiced in the context of worship, but are also used and practiced in social, political, cultural and educational contexts. In the context of Islamic education in the archipelago, it can be realized in the daily life of students by providing activities in schools to produce students who are cultured and have good morals. Education is a place to help build the nation's future to produce a generation that is ready to follow the challenges of the times. Therefore, education has a big enough contribution to equip students to be able to keep up with the increasingly dynamic times. The affective aspect in education has not become the main one. This is because the current shift in the foundation of educational goals can be seen from the fact that schools prioritize cognitive aspects to produce students who excel in knowledge of each subject so that they do not equip students and instill values ​​in students that are useful in everyday life. day. So that the problems above have a negative impact on the world of education, namely the decline in the morals of students. Today, there are many cases involving junior high school (SMP) or MTS students, including taking drugs, committing sexual crimes, getting angry easily, being very emotionally unstable, having no respect for parents and teachers and preferring to follow Western cultural trends in daily life. Such incidents must be followed up immediately, one of which is by maximizing value education in schools that will make a good contribution to students both inside and outside of school. So the implementation of the Islamic values ​​of the archipelago is one of the right solutions in equipping students to be cultured in accordance with Islamic teachings and have noble character in living their daily lives.